Crux Criticorum: Matt. Xi. 25–30 : A Re-Appraisal - Hunter, A. M. (New Testament studies, 1962)
These are perhaps the most important verses in the Synoptic Gospels. Discussing them in 1927, the late Claude Montefiore2 candidly confessed that, as a Jew, he would like to prove them spurious because, if it could be shown that Jesus had really uttered them, orthodox Christianity would have received notable encouragement. This however, he judged very unlikely, and he went on to predict that, as the years went by, the voices raised in defence of their authenticity would grow feebler and fewer.